Clinical Evaluation of Different Minimal Invasive Treatment Modalities of Mild to Moderate Dental Fluorosis Using an Intra-oral Spectrophotometer - Youssef, M. N.; Abo Elezz, A. F.; Elddamony, E. A.; Ghoniem, A. F. (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Various treatment modalities are available to improve esthetics of fluorosed teeth based on its severity. AIM: The aim of the study was to evaluate the clinical performance of different minimal invasive treatment protocols on mild to moderate fluorosed teeth. METHODS AND MATERIALS: Before the interventions, tooth color coordinates L, a and b were recorded for 160 fluorosed teeth by Vita Easyshade V. Participants were randomly allocated in eight treatment protocols with 20 teeth (n = 20) included in each protocol. Protocol one (P1) Opalescence boost PF 40%. Protocol two (P2) Opalustre. Protocol three (P3) MI-Paste Plus. In protocol four (P4) teeth were treated with Opalustre followed by Opalescence boost PF 40%. In protocol five (P5) Opalescence boost PF 40% was applied followed by MI-Paste Plus, while in protocol six (P6) Opalustre was applied followed by MI-Paste Plus whereas protocol seven (P7) teeth were treated with Opalustre, followed by Opalescence boost PF 40% and finally MI-Paste Plus. Protocol eight (P8) control. All teeth were evaluated immediately for color change (ΔE) after treatment (T1), after 14 days (T2), after 3 months (T3) and after 6 months (T4). Color change (ΔE) was calculated from ΔL, Δa, and Δb recorded at each evaluation time point. STATISTICAL ANALYSIS: Two-way ANOVA was applied to test the interaction between different variables. ANOVA repeated measures were followed by Duncan multiple range tests (DMRTs) to compare between groups. RESULTS: In accordance to time, all treatment protocols showed significant color change can be recognized by unexperienced eye (ΔE ≥ 3.7). Immediately after application (T1), the highest color change (ΔE) was recorded in P7. While at 14 days and 3 months follow ups, color change in P4 exceeded P7. After 6 months the highest ΔE was recorded in both P4 and P7 with no significant difference between them. Meanwhile, in Accordance to treatment Protocol, The highest color change was recorded at 3 months (T3) in all treatment protocols. These records were preserved at 6 months follow-up (T4) for all treatment protocols except P1 and P3. CONCLUSION: Combined treatment protocols of Opalustre and Opalescence boost PF 40% have the highest effect on ΔE regardless of using MI-Paste Plus. MI-Paste Plus provides stability of ΔE results at 6 months’ follow-up.